Motivation to donate surplus Food in Malaysia Retail Industry / Saidatul Akma Hamik, Ahmad Fariz Mohamed and Mizuho Sato - Hamik, Saidatul Akma; Mohamed, Ahmad Fariz; Sato, Mizuho (2021)
In the food industry, waste occurs throughout the supply chain, with an estimated 35% occurring at the point of final consumption (FAO 2011, 2013; Lipinski et al., 2013). Reducing food waste is a challenge for food and waste policies. The quantity of food wasted varies between countries, primarily determined by income, industrialisation, and level of development (Abiad & Meho, 2018; Chalak et al., 2016). United Nations Food and Agriculture Organization estimated monthly waste per capita about 25 kilograms in Europe and United States, 18 kilograms in Latin America, and 10 kilograms in South and Southeast Asia (Gustavsson e al., 2011). Socio-cultural, economic, and infrastructure factors in food waste management can influence food waste generation throughout the food supply chain (Thi et al., 2015). In the United States, most food waste is generated at the retail and consumption stages (Garcia-Garcia et al., 2015). However, due to a lack of technology, transportation, and expertise in food preservation in Southeast Asia, most food waste is generated during the production stage (Yang et al., 2016). In Malaysia, the average household generates about 0.5kg to 0.8kg of food waste per day (Chien Bong et al., 2017). Food waste accounts for nearly 63.1 percent of total solid waste components (Karim Ghani et al., 2013). Thus, reducing food waste generated along food supply chains is critical for sustainable food waste management (SFWM). SFWM is a systematic approach in reducing food waste and its impact across the entire food supply chain, from production (agriculture), manufacturing, distribution and retail, consumption, and final disposal (EPA, 2021). Such efforts are consistent with the Sustainable Development Goals 12 (SDG), SDG Target 12.3 aiming to reduce global food waste at retail and consumption stages by half by 2030 (United National, 2015).